Characterization of Different Capsicum Varieties by Evaluation of Their Capsaicinoids Content by High Performance Liquid Chromatography, Determination of Pungency and Effect of High Temperature - Alberto González-Zamora; Erick Sierra-Campos; J. Guadalupe Luna-Ortega; Rebeca Pérez-Morales; Juan Carlos Rodríguez Ortiz; José L. García-Hernández (Molecules, 2013)
The chili pepper is a very important plant used worldwide as a vegetable, as a spice, and as an external medicine. In this work, eight different varieties of Capsicum annuum L. have been characterized by their capsaicinoids content. The chili pepper fruits were cultivated in the Comarca Lagunera region in North of Mexico. The qualitative and quantitative determination of the major and minor capsaicinoids; alkaloids responsible for the pungency level, has been performed by a validated chromatographic procedure (HPLC-DAD) after a preliminary drying step and an opportune extraction procedure. Concentrations of total capsaicinoids varied from a not detectable value for Bell pepper to 31.84 mg g−1 dried weight for Chiltepín. Samples were obtained from plants grown in experimental field and in greenhouse without temperature control, in order to evaluate temperature effect. Analysis of the two principal capsaicinoids in fruits showed that the amount of dihydrocapsaicin was always higher than capsaicin. In addition, our results showed that the content of total capsaicinoids for the varieties Serrano, Puya, Ancho, Guajillo and Bell pepper were increased with high temperature, while the content of total capsaicinoids and Scoville heat units (SHU) for the varieties De árbol and Jalapeño decreased. However, the pungency values found in this study were higher for all varieties analyzed than in other studies.